Ritual Brobosan Sebagai Penghormatan Terakhir dalam Liturgi Pemakaman Jawa-Kristiani - Wimbodo Purnomo, Agustinus (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2017)
The Catholic Church provides occasions for funeral rites so as to illuminate the death of the faithful within the paschal mystery of Christ. The Church administers the funeral and offers prayers for its departing members to escort them to the afterlife. Funeral ceremonies are held to comfort the bereaved family, but also to strengthen the faith of the people. Therefore, the funeral ceremony could be seen as a pastoral means to foster the faith of the believers and at the same time to evangelise the gospel. Inculturation could be seen as a process to help the faithful experience God’s saving presence in the liturgy from their respective cultures. In this article, the author views the funeral of the faithful as an entrance for inculturation, bringing Christian liturgy towards the local culture, which in this paper is the Javanese culture, and vice versa. The Javanese culture has its own philosophy in escorting the departing souls through its rituals. This article attempts to integrate what has been a ritual of death in the Javanese culture, i. e. brobosan, which shows a gesture of giving respect to the departed, in the Catholic funeral liturgy, particularly in the last part of the rite.